Binomial order is a speech marker of psychosis and thought disorder - Alice Luo; Jintian Luo; Michael Murphy (Scientific Reports)
Abstract Thought disorder, characterized by disruptions in syntactic and semantic elements in language, is a core symptom of psychotic disorders. Understanding this language impairment is key to uncovering the underlying neuropathology and predicting treatment outcomes for individuals with schizophrenia and other psychotic disorders. Binomial ordering preferences (e.g. “salt and pepper” instead of “pepper and salt”), may be a quantifiable correlate of thought disorder and underlying linguistic impairments. We tested whether atypical binomial ordering can serve as a linguistic marker for psychosis symptoms. Participants with early-stage psychotic disorders and controls were recruited, and video-recorded interviews were transcribed for analysis. Identified binomial pairs were assessed using both the Google N-gram database and a logistic regression model to determine ordering preferences. Results showed that while both psychotic participants and controls preferred conventional binomial orderings, participants with psychotic disorders exhibited a higher rate of atypical binomial orderings. The use of atypical orderings was correlated with thought disorder, but not with other psychiatric symptoms or medications. Tracking binomial ordering can be a valuable marker of thought disorder but future studies are needed to determine whether this link remains stable or if it changes with disease progression.